Pengaruh Masase Kaki Dan Rendam Air HangatPada Kaki Terhadap Penurunan Insomnia Pada Lansia - Edy Prananto, Andrian; , Arina maliya,S.Kep.M.Si. Med (2016)
Body systems in the elderly will experience a decline in various aspects like a biological, physiological, psychosocial, and spiritual, is an aging one is difficulty sleeping disorders (insomnia). Treatment of insomnia in elderly can be cured with pharmacological and non-pharmacological. One type of nonpharmacological treatment of insomnia in elderly is a massage therapy (massage) and soak feet in warm water. This research aims to determine the effect of foot massage and warm water soak the feet to the decline of elderly's insomnia. This research is a quantitative research with quasi-experiment and nonequivalent control group design with pre-post test design. Sample of the research was 15 elderly in a nursing Wreda Dharma Bakti Pajang Surakarta as the experimental group, namely the group given massage therapy and soak your feet in warm water and 15 elderly in Griya PMI Peduli Surakarta as the control group were selected by simple random sampling technique. The collection of data obtained from the observation sheet Insomnia Rating Scale. Data analysis was performed using analysis of paired sample t-test and independent sample t-test. The results showed that the test results paired sample t-test there is no difference in the average insomnia pre-test and post-test in the control group (p-value = 0.104), and there are differences in the average insomnia pre test and post test experimental group (p-value = 0.001). The test results of independent sample t-test result that there is no difference in the average insomnia pre-test between the experimental group and control group (p-value = 0.621) and there are differences in the average insomnia post test between the experimental group and control group (p-value = 0.001). Keywords: insomnia, elderly, massage therapy, therapeutic warm water soaks.